2009
DOI: 10.1017/s0007114509359097
|View full text |Cite
|
Sign up to set email alerts
|

Plant foods and the risk of cerebrovascular diseases: a potential protection of fruit consumption

Abstract: Studies on the association between plant foods and cerebrovascular diseases have given contradictory results suggesting the existence of some effect-modifying factors. The present study determines whether the consumption of plant foods (i.e. fruits and berries, vegetables, and cereals) predicts a decreased cerebrovascular disease incidence in a population with low fruit and vegetable and high wholegrain intake. This cohort study on 3932 men and women was based on data from the Finnish Mobile Clinic Health Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 40 publications
2
91
1
Order By: Relevance
“…The β coefficients of circulating carotenoids, tocopherol and folate (Table 3) between children who did not consume or rarely consumed F&V (FFI 0 ) and each category of consumption of F&V, including the grouping FFI [1][2][3][4] , showed statistically significant differences for carotenes and tocopherol in all FFI categories (except for FFI 4 ). Regarding serum folate concentration, differences according to categories of F&V consumption were not observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The β coefficients of circulating carotenoids, tocopherol and folate (Table 3) between children who did not consume or rarely consumed F&V (FFI 0 ) and each category of consumption of F&V, including the grouping FFI [1][2][3][4] , showed statistically significant differences for carotenes and tocopherol in all FFI categories (except for FFI 4 ). Regarding serum folate concentration, differences according to categories of F&V consumption were not observed.…”
Section: Resultsmentioning
confidence: 99%
“…*FFI 0 , consumption of vegetables never or ≤ 3 times/month and fruits ≤ 3 times/week; FFI [1][2][3][4] , consumption of vegetables ≥ 1 time/week and fruits ≥ 4 times/week. †VDI defined as serum vitamin D < 75 nmol/l; ND defined as having at least one of the nutritional disturbances except for VDI; VAD defined as serum retinol < 0·70 µmol/l; VEI defined as serum tocopherol < 11·61 µmol/l; anaemia defined as Hb < 110·0 g/l for children under 5 years and Hb < 115·0 g/l for children aged 5-10 years; FD defined as serum folate < 10 nmol/l; stunting defined as HAZ < − 2; obesity defined as BMIZ > 2.…”
Section: Discussionmentioning
confidence: 99%
“…Legume consumption and stroke risk Six studies (19,21,22,26,27,29) comprising eight data sets were considered for the analysis on the highest v. lowest level of dietary legume intake and stroke risk. The pooled analysis showed null results with no substantial risk increment or reduction for higher consumption of legumes (RR = 1·01; 95 % CI 0·89, 1·14).…”
Section: Legume Consumption and Cvd Risk 249mentioning
confidence: 99%
“…Among the thirty-four articles obtained after screening on the basis of title and abstract, twenty studies were excluded after a full-text examination because they were not relevant for the research (n 11), did not study CVD as outcome (n 3), had a study design other than prospective (n 2), reported insufficient statistics (n 2), were conducted on the same cohort of another study but had shorter follow-up (n 1) or considered composite legume and other foods consumption (n 1). This inclusion strategy resulted in the final inclusion of fourteen studies (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and thirty-two data sets eligible to be considered for the quantitative analysis. Studies included were conducted on eleven cohorts and accounted for a total of 367 000 individuals and 18 475 cases of CVD, including 7451 CHD and 6336 stroke cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation